Morphologic and molecular evaluation of Chlamydia trachomatis growth in human endocervix reveals distinct growth patterns - Lewis, Maria E.; Belland, Robert J.; AbdelRahman, Yasser M.; Beatty, Wandy L.; Aiyar, Ashok A.; Zea, Arnold H.; Greene, Sheila J.; Marrero, Luis; Buckner, Lyndsey R.; Tate, David J.; McGowin, Chris L.; Kozlowski, Pamela A.; et al. (Frontiers in Cellular and Infection Microbiology, 2014)
In vitro models of Chlamydia trachomatis growth have long been studied to predict growth in vivo. Alternative or persistent growth modes in vitro have been shown to occur under the influence of numerous stressors but have not been studied in vivo. Here, we report the development of methods for sampling human infections from the endocervix in a manner that permits a multifaceted analysis of the bacteria, host and the endocervical environment. Our approach permits evaluating total bacterial load, transcriptional patterns, morphology by immunofluorescence and electron microscopy, and levels of cytokines and nutrients in the infection microenvironment. By applying this approach to two pilot patients with disparate infections, we have determined that contrasting growth patterns correlate with strikingly distinct transcriptional biomarkers, and are associated with differences in the levels of IFNγ in the endocervix. Our multifaceted approach will be useful to dissect infections in the human host and be useful in identifying patients at risk for chronic disease. Importantly, the molecular and morphological analyses described here indicate that persistent growth forms can be isolated from the human endocervix when the infection microenvironment resembles the in vitro model of IFNγ−induced persistence.